Peran Guru Laki-Laki Pada Lembaga PAUD Ditinjau dari Perspektif Fungsi Afeksi di Tk Aisyiah Bustanul Athfal 1 Ngawi - Wiwit Purnama Putri; Narendradewi Kusumastuti; Arwendis Wijayanti (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2022)
The phenomenon of the lack of male participation in ECEC, makes children not get the full role of men when they are in school. The purpose of this study was to determine the form, role, and inhibiting and supporting factors of the role of male teachers in ECEC institutions from the perspective of the affective function. The research subjects were male teachers at TK Aisyiah Bustanul Athfal 1 Ngawi. The type of research is qualitative research with a phenomenological approach. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that the role of male teachers in ECEC institutions has a positive impact on the learning process in the classroom and outside the classroom. Forms of the role of male teachers that appear such as providing children with support, attention and protection. The process of forming the role of male teachers is by approaching, reading often, attending training, and exchanging opinions with fellow teachers, about how to understand students and adapt to the ECEC environment. The formation of the role of male teachers in ECEC institutions from the perspective of affective functions, cannot be separated from the support factor of parents, school principals, and fellow teachers at TK Aisyiah Bustanul Athfal 1 Ngawi.